2016
DOI: 10.1016/j.jns.2016.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Haemorrhagic transformation in ischaemic stroke is more frequent than clinically suspected – A neuropathological study

Abstract: ObjectivesThe vast majority of literature on the frequency of the haemorrhagic transformation of ischaemic stroke is based on imaging studies. The purpose of the present study was to assess the added value of autopsy and neuropathological analysis in a neurology centre with emphasis on acute stroke care. MethodsWe retrospectively analysed the findings of 100 consecutive brain autopsies followed by detailed clinical correlation. ResultsThe clinical diagnosis was confirmed by neuropathology in every patient with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(50 reference statements)
2
4
0
Order By: Relevance
“…Studies from Singapore and south east Asian populations suggest that the frequency of haemorrhagic stroke is higher than in the Caucasian population 22 , however the overall frequency of ischaemic stroke remains high in Asian populations 23 . As compared to our data, in earlier studies by Hornig et al, HT was observed in 28 out of 65 patients (43%) over a four-week period 3 , and the frequency of HT was 29% in one neuropathological study 4 . The percentage of HT in studies of stroke patients varies from 6.4 to 43% 7,11,15,17,[24][25][26][27][28][29] .…”
Section: Discussionsupporting
confidence: 65%
“…Studies from Singapore and south east Asian populations suggest that the frequency of haemorrhagic stroke is higher than in the Caucasian population 22 , however the overall frequency of ischaemic stroke remains high in Asian populations 23 . As compared to our data, in earlier studies by Hornig et al, HT was observed in 28 out of 65 patients (43%) over a four-week period 3 , and the frequency of HT was 29% in one neuropathological study 4 . The percentage of HT in studies of stroke patients varies from 6.4 to 43% 7,11,15,17,[24][25][26][27][28][29] .…”
Section: Discussionsupporting
confidence: 65%
“… 24 25 In an earlier autopsy study conducted at our clinic (in 64 patients with cerebral ischaemia), we found haemorrhagic transformation of an infarct in 38% of the patients. 26 This proportion was similar in the present study (in over half thousand patients): we found a rate of 35%. A haemorrhagic transformation of an infarct increases both early and late mortality after ischaemic stroke.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence rate reported in literature only depends on whether CT-reported transformations (13%–43%) or asymptomatic/symptomatic cases (0.6%–20%) were considered 24 25. In an earlier autopsy study conducted at our clinic (in 64 patients with cerebral ischaemia), we found haemorrhagic transformation of an infarct in 38% of the patients 26. This proportion was similar in the present study (in over half thousand patients): we found a rate of 35%.…”
Section: Discussionmentioning
confidence: 71%
“…Increased BBB permeability leading to cerebral oedema [ 68 , 79 ] and haemorrhagic transformation [ 80 , 81 ] are common complications of ischaemic stroke, which can impact the outcome of these patients with potential serious and life-threatening consequences [ 82 ]. A series of factors or events in combination or in sequence can lead to BBB disruption in ischaemic stroke.…”
Section: Mechanisms Of Bbb Disruptionmentioning
confidence: 99%